Eksplorasi Etnomatematika pada Pembuatan Kubah Masjid Berbahan Stainless Steel sebagai Bahan Lembar Kerja Siswa - Annisa, Nurul; Sugiarti, Titik; Monalisa, Lioni Anka; Sunardi, Sunardi; Trapsilasiwi, Dinawati (Kadikma, 2020)
Ethnomatics are cultural practices related to mathematical activities such as grouping, counting, calculating, designing buildings or tools, determining locations. This research was conducted at the Soponyono Dome Company, Wirolegi, Jember. The purpose of this study is to describe ethnomatematics in the manufacture of stainless steel mosque domes and produce student worksheets. This research is a type of qualitative research with ethnographic approach. Data collection methods used are observation, interviews and documentation. The subjects of this research are the owner of the company and four dome craftsmen. Geometry concepts or elements found include: congruent, flat shapes (rectangle, irregular hexagon, circle segment, trapezoid), space structures (cylinder, truncated ball, cone, and truncated cone), geometrical transformations (dilatation), and mathematical activity (measuring activity, counting activity, and design activity). The results of the study were made as worksheet material for Grade IX students with the subject of constructing curved side spaces of tube and cone material. Keywords: Ethnomatematics, Mosque Dome, Student Worksheet.